2019
DOI: 10.2169/internalmedicine.1514-18
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-media Thickness and Small Dense Low-density Lipoprotein Cholesterol Increase after One Year of Treatment with Direct-acting Antivirals in Patients with Hepatitis C Virus Infection

Abstract: Objective Direct-acting antivirals (DAAs) for treating hepatitis C virus (HCV) infection exert a significantly high sustained viral response (SVR), and patients experience a rebound increase in low-density lipoprotein cholesterol (LDL) and total cholesterol levels. Carotid intima-media thickness (IMT) is a highly reproducible and non-invasive parameter for assessing the atherosclerotic process, and the small dense (sd) LDL level is useful for clinically evaluating the atherogenic risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…The authors observed that a small dense LDL-C was associated with the increase in intima thickness. 207 Another report found a significant improvement of tricuspid annular plane systolic excursion and lateral E' velocity relative to baseline values, following SVR to DAA in HCV cirrhotic patients. 208 Central artery stiffness was also increased following HCV clearance as a result of DAA treatment and was related to an increase in LDL-C. 209 Long-term results addressing these paradoxical findings in terms of vascular parameters and the risk of cardiovascular events following viral clearance would be worth investigating.…”
Section: Chroni C Hepatitis Vir Al Infec Ti On and Arteri Oscleros Ismentioning
confidence: 96%
See 1 more Smart Citation
“…The authors observed that a small dense LDL-C was associated with the increase in intima thickness. 207 Another report found a significant improvement of tricuspid annular plane systolic excursion and lateral E' velocity relative to baseline values, following SVR to DAA in HCV cirrhotic patients. 208 Central artery stiffness was also increased following HCV clearance as a result of DAA treatment and was related to an increase in LDL-C. 209 Long-term results addressing these paradoxical findings in terms of vascular parameters and the risk of cardiovascular events following viral clearance would be worth investigating.…”
Section: Chroni C Hepatitis Vir Al Infec Ti On and Arteri Oscleros Ismentioning
confidence: 96%
“…It measured intima thickness following DAA treatment and found that the maximal intima thickness was higher after 1 year of treatment than the baseline value. The authors observed that a small dense LDL‐C was associated with the increase in intima thickness . Another report found a significant improvement of tricuspid annular plane systolic excursion and lateral E' velocity relative to baseline values, following SVR to DAA in HCV cirrhotic patients .…”
Section: Chronic Hepatitis Viral Infection and Arteriosclerosismentioning
confidence: 96%
“…Hypolipidemia during viremic status can be reversed to deteriorate lipid profiles after DAA therapy [ 59 ]. An increase in the small dense low-density lipoprotein cholesterol level corresponding to increased carotid intima-media thickness 1 year after DAA therapy has been reported [ 60 ]. Attention should be paid not only to liver-related complications but also to the extrahepatic consequence of cardio-cerebrovascular disease in the post-SVR period.…”
Section: Post-svr Eramentioning
confidence: 99%
“…Atherosclerosis is an important contributor for sexual dysfunction (Gowani et al., 2017; Miner et al., 2019). The DAA therapy had advantage of improvement of atherosclerosis (Butt et al., 2019; Ichikawa et al, 2019) and therefore is beneficial in sexual function in patients with HCV.…”
Section: Discussionmentioning
confidence: 99%